2017
DOI: 10.1097/bcr.0000000000000444
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Altered the Skeletal Muscle MicroRNAs and Gene Expression Profiles in Burn Rats With Hindlimb Unloading

Abstract: Objective This study investigated microRNA and target gene profiles under different conditions of burn, bed rest, and exercise training. Methods Male Sprague-Dawley rats (n = 48) were assigned to sham ambulatory, sham hindlimb unloading, burn ambulatory, or burn plus hindlimb unloading groups. Rats received a 40% total body surface area scald burn or sham treatments and were ambulatory or hindlimb unloaded. Rats were further assigned to exercise or no exercise. Plantaris tissues were harvested on day 14 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The possible pathway involved an miRNA 140-negative interaction with Mfn1 in cardiomyocyte apoptosis (36). Our previously published study showed that miR-140–3p related to mitochondrial dynamics regulation increased 1.17 fold in plantaris muscle from 40% TBSA burn rats 14 days later (37). …”
Section: Discussionmentioning
confidence: 99%
“…The possible pathway involved an miRNA 140-negative interaction with Mfn1 in cardiomyocyte apoptosis (36). Our previously published study showed that miR-140–3p related to mitochondrial dynamics regulation increased 1.17 fold in plantaris muscle from 40% TBSA burn rats 14 days later (37). …”
Section: Discussionmentioning
confidence: 99%
“…Considering the tendon as the connector and force transmitter between skeletal muscle and bone, it is essential to understand tendon's behavior in response to severe injury. Future investigation regarding the modulation of the inflammatory cascade and MMP inhibition accompanied by regulated physical therapy that allows proper tissue loading to prevent disuse, but also prevent overuse ( 31 35 ) may be promising for the improvement of recovery after severe burn and other traumatic injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of muscle force‐generating capacity associated with mechanical unloading is well established (Table ). Thus, numerous studies show that HU results in a reduced force‐generating capacity of the hindlimb muscles in rats and mice . Muscle weakness is partly because of reduced muscle mass but defect in the intrinsic force‐generating capacity of skeletal muscle also contributes.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, numerous studies show that HU results in a reduced force-generating capacity of the hindlimb muscles in rats and mice. [56][57][58][59][60] Muscle weakness is partly because of reduced muscle mass but defect in the intrinsic force-generating capacity of skeletal muscle also contributes. These findings are translated to single muscle fibres, which show reduction in the force/cross-sectional area (specific force) during muscle unloading.…”
Section: Changes In the Muscle Forcegenerating Capacitymentioning
confidence: 99%